Peramalan Kebutuhan Energi Jual pada PT Perusahaan Listrik Negara (PLN) Cabang Bukittinggi dengan Menggunakan Metode Dekomposisi Sensus Ii - Sujantri Wahyuni; Helma Helma; Nonong Amalita (UNIVERSITAS NEGERI PADANG, 2014)
Abstract – Indonesia’s electrical are managed by PT.PLN. To increase distribution service of electric in all of area. PT PLN could forecast necessity of sell energy, so that could planning energy will be distribution based result of forecasting. Pattern of sell energy is seasonal pattern. Decomposition census II is realiable for seasonal pattern. This research study about how much necessity of sell energy for 12-monthly by decomposition census II ? The result based description of data and analisis of data are necessity of sell energy is between 28.537.128 until 33.359.590 Keywords: forecast, Decomposition census II, necessity of sell energy